Variation of material parameters for the thickness extensional mode of piezoceramic discs in case of mechanical loading - Rupitsch, Stefan; Ilg, Jürgen; Sutor, Alexander; Lerch, Reinhard (Elsevier BV, 2011)
Here, we report on the variation of material parameters of piezoceramic discs due to applied static and isotropic mechanical loads. Such mechanical loads frequently occur in piezoelectric sensor and actuator devices. In order to achieve reliable results from numerical simulation tools, these mechanical loads need to be taken into account. However, as alternative to considering the static and isotropic mechanical loads within the numerical simulation, we alter the material parameters of the piezoceramic appropriately. The material parameters for different mechanical loads are estimated by means of a mathematical Inverse Method. As the results for the thickness extensional mode of two different piezoceramic discs clearly show, primarily three material parameters are influenced by mechanical loads up to 2.0 MPa. (C) 2011 Published by Elsevier Ltd.
Keywords: Piezoceramics disc; Thickness extensional mode; Inverse Method; Electrical behavior; Mechanical load